Inhibition of hepatitis B virus surface gene expression by antisense oligodeoxynucleotides in a human hepatoma cell line - Reinis, M; Reinisová, M; Korec, E; Hlozánek, I (Folia biologica, 1993)
We have studied the inhibitory effect of antisense oligodeoxynucleotides on the expression of hepatitis B virus surface antigens. Human hepatoma cell line PLC/PRF/5 harbors several integrated copies of the HBV genome and produces and secretes hepatitis B virus surface antigen (HBsAg) to the medium. Synthetic antisense oligodeoxynucleotides complementary to various regions of the surface antigen gene were synthesized and their ability to block its expression was tested. Oligodeoxynucleotides (17- and 21-mers) complementary to regions covering ATG codons of both preS2 and S genes significantly inhibited preS2 and S protein production. Less efficient inhibition was achieved when the oligonucleotide complementary to the inside S gene region was assayed.
Keywords: Viral Structural Proteins; Genes, Viral; molekulární sekvence - údaje; buněčné linie; messenger RNA; regulace exprese virových genů; RNA, Messenger; Base Sequence; virus hepatitidy B; virové geny; Gene Expression Regulation, Viral; lidé; virové strukturální proteiny; Molecular Sequence Data; ELISA; hepatocelulární karcinom; Hepatitis B Surface Antigens; Cell Line; Oligonucleotides, Antisense; Hepatitis B virus; Humans; Carcinoma, Hepatocellular; sekvence nukleotidů; Enzyme-Linked Immunosorbent Assay; hepatitida B - antigeny povrchové; antisense oligonukleotidy